(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Deforestation, which is when forests are cleared on a large scale, plays a important role in climate change and is largely responsible for rising global temperatures. Forests are like nature’s air filters; they absorb and store carbon dioxide (CO2), a greenhouse gas that contributes to warming our planet. But when we chop down trees for agriculture, urban development, and industries, all that stored carbon is released back into the atmosphere, making climate change even worse. In this paper, we’ll dive into how deforestation directly and indirectly affects the environment, climate, and communities around the world. We’ll look at the science behind deforestation, how it disrupts the carbon cycle, and the broader impacts on biodiversity, weather patterns, and human society. Plus, we’ll suggest ways to help combat deforestation, like supporting conservation efforts, adopting sustainable land-use practices, and making policy changes. A team effort involving governments, businesses, and local communities is critical to tackle the ongoing crisis of deforestation and its role in climate change.